Surviving the Oregon Trail, 1852 - Rau, Weldon W. (Book collections on Project MUSE., 2001)
The 1852 overland migration was the largest on record, with numbers swelled by Oregon-bound settlers as well as hordes of gold-seekers destined for California. It also was a year in which cholera took a terrible toll in lives. Included here are firsthand accounts of this fateful year, including the words and thoughts of a young married couple, Mary Ann and Willis Boatman.